The Implementation of China's Mental Health Law-Defined Risk Criteria for Involuntary Admission: A National Cross-Sectional Study of Involuntarily Hospitalized Patients - Jiang, Feng; Zhou, Huixuan; Rakofsky, Jeffrey J.; Hu, Linlin; Liu, Tingfang; Liu, Huanzhong; Liu, Yuanli; Tang, Yi-lang (Frontiers in Psychiatry, 2018)
Objective: Involuntary admission is one of the most controversial issues in psychiatry in China. This study aimed to examine the implementation of the criteria for involuntary admission, as defined by the new Mental Health Law (MHL), in major psychiatric hospitals, and to explore factors associated with the variation in implementation. Method: We selected 32 psychiatric hospitals in 29 provincial capital cities in mainland China. We included all involuntarily admitted psychiatric inpatients who were discharged from December 25 to 27, 2017. Patients’ demographic and clinical data and reasons for admission were retrieved. Hospitals’ information was also collected. Multilevel logistic regression was applied to estimate variation in risk criteria implementation. Result: We collected valid data from 814 involuntarily admitted patients. Rates of implementation ranged from 7.9% to 88.5% in these hospitals. Only 369 inpatients (45.3%) met the MHL-defined risk criteria. Overall, between 62.2% and 78.5% of the variance in risk criteria implementation was at the patient level, and between 21.5% and 37.8% of the variance was at the hospital level. Patients with higher Global Assessment of Functioning (GAF) scores at admission were less likely to meet the risk criteria (OR 1.02, 95% CI 1.01-1.03). No statistically significant association was found between risk criteria implementation and other patient level or hospital level factors. Conclusion: Our findings show the implementation rate of the MHL’s risk criteria overall was low, with only 45.3% of involuntary admissions meeting the MHL-defined criteria. This suggests that some patients’ civil rights might have been violated.